STUDI PEMBALIKAN POLARISASI DAN MODEL HISTERISIS PADA MATERIAL LAPISAN TIPIS BARIUM STRONSIUM (Ba0,5 Sr 0,5TiO3 ) DIDADAH Pb, Mg dan Cu - Yoga Raksa, Teguh; Hikam, Muhammad; Iriani, Yofentina (Jurnal Spektra, 2014)
Switching phenomenon inBIST thin film will be studiedusing bulk ferroelectric material approach. Static and dynamic Â approach will be formulated by combination of Landau â Devonshire (LD) and Landau â Kalatnikov (LK) equation to determined maximum and minimum of switching current. Hysteresis loop was developed using sinusoidal electrical field Â response by variation in frequency and amplitude of electrical field to describe hysteresis model of BST. Keywords: Switching Phenomenon , Hysterisis Model, Landau Theory,BST